Capital budgeting in investment and project appraisal / Wong Soon Heng - Wong, Soon Heng (UiTM cawangan Kedah, 2002)
This article critically evaluates the relative attractions of the Net Present Value (NPV) method in capital budgeting. The author argues for the NPV method over the Internal Rate of Return (IRR) method. The implications of inflation for investment appraisal are discussed in the later part of this article. The author opines that in capital budgeting, particularly for projects with a long life, the inflation factor cannot be ignored.